2023
DOI: 10.3390/s23020995
|View full text |Cite
|
Sign up to set email alerts
|

Review of Sensor Technology to Support Automated Air-to-Air Refueling of a Probe Configured Uncrewed Aircraft

Abstract: As technologies advance and applications for uncrewed aircraft increase, the capability to conduct automated air-to-air refueling becomes increasingly important. This paper provides a review of required sensors to enable automated air-to-air refueling for an uncrewed aircraft, as well as a review of published research on the topic. Automated air-to-air refueling of uncrewed aircraft eliminates the need for ground infrastructure for intermediate refueling, as well as the need for on-site personnel. Automated ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Firstly, the sheer act of transporting vast quantities of fuel across the airport uses substantial energy. Secondly, given the emissions associated with diesel combustion, they contribute significantly to the airport's overall carbon footprint (Li and Zhang 2023;Mangold et al 2022;Parry and Hubbard 2023). Furthermore, consider the auxiliary power needs of an aircraft during its layover.…”
Section: Ground Support Activitiesmentioning
confidence: 99%
“…Firstly, the sheer act of transporting vast quantities of fuel across the airport uses substantial energy. Secondly, given the emissions associated with diesel combustion, they contribute significantly to the airport's overall carbon footprint (Li and Zhang 2023;Mangold et al 2022;Parry and Hubbard 2023). Furthermore, consider the auxiliary power needs of an aircraft during its layover.…”
Section: Ground Support Activitiesmentioning
confidence: 99%
“…However, UAVs are severely limited in their potential applications because of their insufficient fuel capacity and short endurance, which prevents them from completing long-duration, long-distance missions. The distance, retention time, activity space, and payload of UAVs may, however, be enormously increased thanks to a technology called unmanned aerial vehicle autonomous aerial refueling (UAV-AAR), without essentially altering the original architecture of the aircraft [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This improves the scale adaptation and real-time performance of the object detection network and successfully realizes the feature extraction and matching of the drogue. (2) We propose a binocular vision-based drogue pose estimation method for the UAV-AAR vision navigation problem, which can effectively complete drogue pose estimation and provide accurate navigation information. In addition, a visual reprojectionbased pose optimization method is proposed, which can further improve the accuracy and robustness of the drogue pose estimation algorithm by using more feature points.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the process can be reliably and cheaply automated then there is the potential to democratize this technology by making it accessible beyond military circles. Thus, revealing the economic advantages highlighted by Nangia [29] and Parry [33], where it is shown that lightweight civilian aircraft could perform longer range flights with enhanced efficiency, thanks to the prospect of automated aerial refueling (AAR). Past attempts at AAR relied on differential Global Positioning System (GPS) and custom data-links to conduct their demonstrations [14,44], thus making the cost untenable and failing to meet the military's need to operate in signal degraded environments.…”
Section: Introductionmentioning
confidence: 99%
“…Inexpensively adding sensors and creating reliable enough autonomy could extend AAR to the civilian community [29,33]. Parry and Hubbard focused on using a vision based approach exclusively for finding the refueling basket immediately before contact, while relying on GPS for all other aspects of the refueling process [33]. This is due to certification concerns with neural networks.…”
Section: Introductionmentioning
confidence: 99%